2019
DOI: 10.30612/re-ufgd.v6i12.10623
|View full text |Cite
|
Sign up to set email alerts
|

Milk quality evaluation of dairy farmers in the Alto São Francisco Region

Abstract: Among family farmers, milk production is one of the main activities developed. The aim of this work was to evaluate the milk quality in the some properties and to monitor or manage the properties for observation of deficient points. The project was conducted on rural properties in the Bambuí / MG city and which works with bovine milk production, saves between 50 and 600 liters per day. The work started on March 2015 and ended on February 2016 and was developed through a partnership with Laticínio Total União L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…A similar situation of interaction between the university and social groups is presented in the article by Oliveira et al (2020), when reporting dialogues and technology transfer between settlers involved in the production of organic products, with university professors and students, a situation that according to the authors "There was a positive socio-environmental and ecological impact for beekeepers with the use of technologies introduced in the transition process to the organic honey production system" (OLIVEIRA, et al, 2020). Peres et al, (2019) performing technical monitoring of small producers in the Alto São Francisco region, in Minas Gerais, from 2015 to 2016, observed that producers who received technical assistance were able to improve the quality of the milk produced, meeting the requirements of the Ministry of Agriculture, Livestock and Supply, for the milk to be considered of good quality, confirming the importance of quality guidance for producers, aiming to increase production and improve the quality of the raw material.…”
Section: Resultsmentioning
confidence: 87%
“…A similar situation of interaction between the university and social groups is presented in the article by Oliveira et al (2020), when reporting dialogues and technology transfer between settlers involved in the production of organic products, with university professors and students, a situation that according to the authors "There was a positive socio-environmental and ecological impact for beekeepers with the use of technologies introduced in the transition process to the organic honey production system" (OLIVEIRA, et al, 2020). Peres et al, (2019) performing technical monitoring of small producers in the Alto São Francisco region, in Minas Gerais, from 2015 to 2016, observed that producers who received technical assistance were able to improve the quality of the milk produced, meeting the requirements of the Ministry of Agriculture, Livestock and Supply, for the milk to be considered of good quality, confirming the importance of quality guidance for producers, aiming to increase production and improve the quality of the raw material.…”
Section: Resultsmentioning
confidence: 87%
“…Therefore, rural producers must have full access to technologies and information that enable them to improve the production process on their property, which are incorporated into the role of technical assistance within the areas of research and academic extension as an integral part of both the student's curriculum and the institutional action in the teaching-research-extension tripod (PERES et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A razão da escolha desta atividade para os pequenos produtores rurais, é que não necessita de muitos investimentos ou grandes áreas para seu desenvolvimento e, por esse motivo, é uma das alternativas indicadas para geração de emprego e renda no campo (ARAÚJO, 2016). Estes produtores representam 61% do total de estabelecimentos rurais e são responsáveis por 44% dos alimentos, sendo os principais intendentes da matéria prima hoje utilizada em indústrias alimentícias leiteiras (PERES et al, 2019).…”
Section: Introductionunclassified